Minority bonding to political self-efficacy: a case study on bonding and bridging social capital and political self-efficacy among adolescents in Finland - Hannuksela, Venla; Tiihonen, Aino (Frontiers in Political Science, 2024)
While social capital is claimed to predict, for example, a higher level of trust, better health, and higher voter turnout, its uneven distribution causes concern in society. In this study, we examine which aspects of social capital are connected to political self-efficacy, which is an important predictor of political participation and associated with for example political interest. According to our knowledge, there is a research gap both in terms of studies focusing on analyzing the effect of minority status on political self-efficacy via social capital and studies analyzing these patterns among adolescents living their formative years. In this article we test this mediating effect of social capital among majority and minority adolescents since minorities can be expected to have relatively more bonding social capital and less bridging social capital. In the Finnish context, this is particularly interesting since the Swedish-speaking minority is praised for its high level of social capital that is suggested to explain a lot of its success ranging from better health to a higher turnout compared with the majority. Analyzing a nationwide dataset of 15–16-year-old students (N = 5,189) completing their final year of comprehensive education in Finland in a multilevel structural equation model, we discover that belonging to the Swedish-speaking minority seems to strengthen bonding social capital (social networks, and community). The civic participation, community, and social networks aspects of social capital are positively connected to the level of political self-efficacy, while generalized trust has no connection to it. All these findings indicate that societies should take measures to strengthen bridging and bonding social capital among both adolescents and minorities.